Modeling production function of enterprise in conditions of uncertainty and risk - D. A. Bezukhov (Путеводитель предпринимателя, 2020)
Enterprise production activity in conditions of uncertainty and external and internal environment risk modeling peculiarities are studied. Theoretical method of modelling production function based on mathematical model at which formal statements taking into account uncertainty and risk factors is given.